2016
DOI: 10.1074/jbc.m115.676817
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory Macrophages Sustain Pyruvate Oxidation through Pyruvate Dehydrogenase for the Synthesis of Itaconate and to Enable Cytokine Expression

Abstract: Upon stimulation with Th1 cytokines or bacterial lipopolysaccharides, resting macrophages shift their phenotype toward a pro-inflammatory state as part of the innate immune response. LPS-activated macrophages undergo profound metabolic changes to adapt to these new physiological requirements. One key step to mediate this metabolic adaptation is the stabilization of HIF1α, which leads to increased glycolysis and lactate release, as well as decreased oxygen consumption. HIF1 abundance can result in the induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
219
6
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 219 publications
(263 citation statements)
references
References 53 publications
16
219
6
5
Order By: Relevance
“…We further demonstrated that the increase in HP [1-13 C]lactate was likely mediated by pyruvate dehydrogenase kinase 1 up-regulation in activated MPs, resulting in regional pyruvate dehydrogenase inhibition. Altogether, our results demonstrate a potential for 13 C MRSI of HP [1- 13 C]pyruvate as a neuroimaging method for assessment of inflammatory lesions. This approach could prove useful not only in MS but also in other neurological diseases presenting inflammatory components.…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…We further demonstrated that the increase in HP [1-13 C]lactate was likely mediated by pyruvate dehydrogenase kinase 1 up-regulation in activated MPs, resulting in regional pyruvate dehydrogenase inhibition. Altogether, our results demonstrate a potential for 13 C MRSI of HP [1- 13 C]pyruvate as a neuroimaging method for assessment of inflammatory lesions. This approach could prove useful not only in MS but also in other neurological diseases presenting inflammatory components.…”
mentioning
confidence: 58%
“…Interestingly, upon activation and subsequent differentiation toward a proinflammatory phenotype MPs undergo metabolic reprogramming that results in increased glycolysis and production of lactate. Hyperpolarized (HP) 13 C magnetic resonance spectroscopic imaging (MRSI) is a clinically translatable imaging method that allows noninvasive monitoring of metabolic pathways in real time. This method has proven highly useful to monitor the Warburg effect in cancer, through MR detection of increased HP [1- 13 C]pyruvate-tolactate conversion.…”
mentioning
confidence: 99%
See 3 more Smart Citations